The Physical and Psychological Health of Migrants in Guangzhou, China - Hongsheng Chen PhD; Zhenjun Zhu PhD; Dongqi Sun PhD; Xingping Wang PhD (SAGE Publishing, 2016)
This study analyzed the health of migrants in 4 types of neighborhood in the city of Guangzhou in China. The research shows that the health of internal migrants in urban villages and private housing neighborhoods is much better than those living in older inner city neighborhoods (which are known as jiefang shequ) and unit neighborhoods (which are known as danwei). The reasons behind this are the facts that the migrants in urban villages tend to be relatively young and there tend to be better social and economic conditions in the private housing neighborhood. Moreover, among the 4 kinds of neighborhood, the gap between psychological health and physical health is the largest in urban villages. In addition, migrants who are younger, have better working conditions, and have higher levels of education have better health scores, and they tend to have more friends in the city, larger houses, better insurance, and more satisfaction with their neighborhood relationships, and they tend to be better adapted to urban life. As for the determinants of health, individual characteristics, community factors, and insurance are the most important factors. Specifically, individual age and age of housing have negative influences on physical health while insurance has a positive effect. This study shows that the type of neighborhood that migrants live in has a great impact on their psychological health, which can be improved by promoting neighborhood environments. Last, we propose that it is necessary to implement different strategies in different communities.